GDF SUEZ Case Study - Evaluation of Capital Structure, Short-Term Financing and Working Capital - Eisenberg, Paul (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
This article analyses the financial structure of GDF SUEZ for the years 2013 – 2014 by the way of a case study. The company, one of the global players of the energy market, offers rich opportunities to test finance theories reaching from the work of Modigliani and Miller (1958) and Altman (1968) to the more recent approaches of working capital analysis by Panigrahi and Chaudhury (2015), to mention but a few. The study shows a company struggling to accelerate sales and to collect receivables, while over relying on costly short-term finance and stretching accounts payable. Thus, GDF SUEZ forgoes prompt payment discounts and loses supplier goodwill. Taken together with declining revenues, the study provides for a company profile raising going concern issues. The paper may be of interest for finance students, scholars and financial reports analysts as it offers a comprehensive real-life study based on commonly accepted financial modelling.